GREEN BONDS AND CARBON EMISSIONS: THE EUROPEAN UNION CASE (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2023)
Purpose: The growing popularity of green bonds has sparked an ongoing debate about their real impact on the environment. The idea behind green bonds is that they provide environmental benefits, such as a reduction in carbon emissions, by financing environmentally friendly projects. The aim of this paper is to examine the relationship between green bond issuance and CO2 emissions in the EU-27 from 2013 to 2017 to determine the validity of this theory.Methodology: Data on green Eurobonds issued in the EU-27 and CO2 emissions in the EU-27 were collected from 2013 to 2017 using the Refinitiv Eikon database. Descriptive statistics and linear correlation were used to investigate the association between green Eurobonds issued and CO2 emissions per capita in the EU-27.Results: The study found that while green bond issuance increased dramatically, from EUR 5 billion in 2013 to EUR 75 billion in 2017, there was only a small decrease in total and per capita CO2 emissions of 3.7% and 4.6%, respectively. Moreover, no significant relationship was found between them.Conclusions: The results suggest that while an increase in green bond issuance indicates a trend toward more sustainable investments, it does not necessarily lead to a proportional decrease in CO2 emissions. Therefore, further research is needed to better understand the association between green bond issuance and carbon emissions and to identify the underlying factors that may influence this relationship.